PERTUMBUHAN DAN HASIL SELADA (Lactuca sativa L.) DENGAN PEMBERIAN PUPUK KANDANG DAN ABU SEKAM PADI DI INCEPTISOL. - Evelyn Evelyn; Kanang S. Hindarto; Entang Inoriah (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2018)
[GROWTH AND LETTUCE YIELD (Lactuca sativa L.) BY GIVING MANURE AND RICE HUSK ASH IN INCEPTISOL]. Increasing market demand for lettuce (Lactuca sativa L.) makes the prospect of developing lettuce very promising. Bengkulu Province is dominated by inceptisol soil types which have low soil fertility, making it less optimal for lettuce growth. Giving organic matter can increase soil fertility through improving soil physical, chemical and biological properties so that it can support the growth of lettuce. This study aims to determine the dosage of manure, the dose of rice husk ash and the optimal dose interaction for lettuce growth and yield. This research was conducted from May 2018 to July 2018 in Medan Baru, Muara Bangkahulu Subdistrict, Bengkulu City. The research design used was a Completely Randomized Design (CRD) consisting of two factors and repeated 3 times. The first factor is the dosage of cow manure with three levels, namely: 0 tons/ha, 15 tons/ha, and 30 tons/ha. The second factor is the dose of rice husk ash which consists of three levels, namely 0 tons/ha, 3 tons/ha, and 6 tons/ha. Data from the observations were analyzed statistically by Analysis of Variance (ANOVA) using the F test at the level of 5%. To determine the dosage of manure, the dose of rice husk ash and the optimal combination of doses for growth and yield of lettuce used the Polynomial Orthogonal method. The results showed that there was no interaction between cow manure and rice husk ash on the growth and yield of lettuce. The effect of cow manure has not shown the optimum dose for growth and yield of lettuce. The addition of manure doses up to 30 tons/ha was able to increase the value of plant height, number of leaves, leaf area, and fresh weighted plant weight of 0.189, 0.038, 0.931 and 0.104 respectively. Giving rice husk ash up to a dose of 6 tons/ha did not have a significant effect on all observed variables.